USM INSTILLS ENTHUSIASM FOR ENTREPRENEURSHIP IN YOUNGSTERS - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 21 February 2017 – Recognising the importance of providing counselling on basic entrepreneurial skills in detail and for practical use to the younger generation, Universiti Sains Malaysia (USM) Centre for CoCurricular Programme, under the Entrepreneurship Programme, held a basic course on entrepreneurship for Company Managers, involving 273 students from 39 schools in Penang recently.